Electrochemiluminescence Aptasensor with Dual Signal Amplification by Silica Nanochannel-Based Confinement Effect on Nanocatalyst and Efficient Emitter Enrichment for Highly Sensitive Detection of C-Reactive Protein - Ning Ma; Shuai Xu; Weidong Wu; Jiyang Liu (Molecules, 2023)
The rapid and sensitive detection of the important biomarker C-reactive protein (CRP) is of great significance for monitoring inflammation and tissue damage. In this work, an electrochemiluminescence (ECL) aptasensor was fabricated based on dual signal amplification for the sensitive detection of CRP in serum samples. The sensor was constructed by modifying a silica nanochannel array film (SNF) on a cost-effective indium tin oxide (ITO) electrode using the Stöber solution growth method. Gold nanoparticles (AuNPs) were grown in situ within the nanochannels using a simple electrodeposition method as a nanocatalyst to enhance the active electrode area as well as the ECL signal. The negatively charged nanochannels also significantly enriched the positively charged ECL emitters, further amplifying the signal. The recognition aptamer was covalently immobilized on the outer surface of SNF after modification with epoxy groups, constructing the aptasensor. In the presence of CRP, the formation of complexes on the recognitive interface led to a decrease in the diffusion of ECL emitters and co-reactants to the supporting electrode, resulting in a reduction in the ECL signal. Based on this mechanism, ECL detection of CRP was achieved with a linear range of 10 pg/mL to 1 μg/mL and a low limit of detection (7.4 pg/mL). The ECL aptasensor developed in this study offers advantages such as simple fabrication and high sensitivity, making promising applications in biomarker detection.